ANALISIS STABILITAS TALUD BRONJONG UIN SUNAN KALIJAGA YOGYAKARTA - Muhammad Rosihun; Endaryanta Endaryanta (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2011)
Talud is a building that was built to prevent the collapse of steep soil or slopeswhere stability can not be guaranteed by the slope itself. The analysis in this finalproject aims to determine whether or not securely retaining wall located at theGadjah Wong River UIN Sunan Kalijaga Yogyakarta, strong bearing on the stabilityof the soil, slide and bolster the influence of the earthquake were included. Method ofstability analysis talud bronjong Gadjah Wong River UIN Sunan Kalijaga Yogyakartausing the formula of the source book Harry Christady Hardiyatmo, Foundations ofEngineering I, 2006, namely in the Terzaghi equations, equations Hansen (1970)and Vesic (1975). Talud Bronjong at Gadjah Wong River UIN Sunan KalijagaYogyakarta secure in looking it from the stability of shift. Talud Bronjong at GadjahWong River UIN Sunan Kalijaga Yogyakarta secure in the stability of the overthrowbecause of Fgl sf. Talud Bronjong at Gadjah Wong River UIN Sunan KalijagaYogyakarta secure in the carrying capacity of land due to Qmax ≤ qa ie 581.4 ≤833.64 KN/m2.Keywords: Analysis, Stability, Talud